Oncogene-like addiction to aneuploidy in human cancers - Girish, Vishruth; Lakhani, Asad A.; Thompson, Sarah L.; Scaduto, Christine M.; Brown, Leanne M.; Hagenson, Ryan A.; Sausville, Erin L.; Mendelson, Brianna E.; Kandikuppa, Pranav K.; Lukow, Devon A.; Yuan, Monet Lou; Stevens, Eric C.; et al. (Science (American Association for the Advancement of Science), 2023)
Most cancers exhibit aneuploidy, but its functional significance in tumor development is controversial. Here, we describe ReDACT (Restoring Disomy in Aneuploid cells using CRISPR Targeting), a set of chromosome engineering tools that allow us to eliminate specific aneuploidies from cancer genomes. Using ReDACT, we created a panel of isogenic cells that have or lack common aneuploidies, and we demonstrate that trisomy of chromosome 1q is required for malignant growth in cancers harboring this alteration. Mechanistically, gaining chromosome 1q increases the expression of MDM4 and suppresses p53 signaling, and we show that TP53 mutations are mutually exclusive with 1q aneuploidy in human cancers. Thus, tumor cells can be dependent on specific aneuploidies, raising the possibility that these “aneuploidy addictions” could be targeted as a therapeutic strategy. Aneuploidies, which are changes in the numbers of whole chromosomes or chromosome arms, are common in cancer, but their contributions to cancer cell survival have been difficult to pinpoint. Girish et al . developed a chromosome-engineering tool to orchestrate the targeted loss of aneuploid chromosome arms and thereby compare isogenic cancer cell lines with and without selected trisomies. The authors discovered that trisomy of chromosome 1q in particular is advantageous to cancer cells and phenocopies the loss of tumor suppressor TP53 signaling. Tumors with this aneuploidy are sensitive to compounds activated by an enzyme encoded on chromosome 1q, suggesting a potential therapeutic approach. —Yevgeniya Nusinovich Specific aneuploidies benefit cancer cells and may be sensitive to treatment